2020
DOI: 10.1136/annrheumdis-2020-216927
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Doppler and tenosynovial fluid analysis in tenosynovitis

Abstract: ObjectiveTo assess Doppler ultrasound (US) and tenosynovial fluid (TSF) characteristics in tenosynovitis within common rheumatic conditions, as well as their diagnostic utility.MethodsSubjects with tenosynovitis underwent Doppler US and US-guided TSF aspiration for white cell count (WCC) and crystal analysis. Tenosynovial Doppler scores (DS) were semiquantitatively graded. TSF WCC and DS were compared using Kruskal-Wallis tests and logistic regression between non-inflammatory conditions (NIC), inflammatory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It has been reported in the literature that USG can be used to determine and score tendon complications. USG has also been used to investigate flexor tendinopathies in patients treated with volar plate fixation of distal radius fractures [13][14][15][16]. We studied the FPL tendon in particular, since it is the closest tendon to bone and, as it is the closest tendon to bone and, therefore, the closest tendon to the volar plate [13,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in the literature that USG can be used to determine and score tendon complications. USG has also been used to investigate flexor tendinopathies in patients treated with volar plate fixation of distal radius fractures [13][14][15][16]. We studied the FPL tendon in particular, since it is the closest tendon to bone and, as it is the closest tendon to bone and, therefore, the closest tendon to the volar plate [13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported on the amount of tendosynovitis found on USG, related to symptomatic and asymptomatic tendon issues after plate implantation [ 13 ]. Another study scored the amount of tenosynovitis with USG in patients with rheumatoid arthritis [ 14 ]. Another study reported that the extensor tendon complications and dorsal screw penetrations were detected through USG examination in patients who were treated with internal fixation with a volar plate.…”
Section: Discussionmentioning
confidence: 99%
“…US-guided intra-tenosynovial GC injections are more accurate, safer, and are more effective than palpatory GC injections for treating inflammatory tenosynovitis [336,337]. When needed for diagnostic purposes, very small amounts of tenosynovial fluid can be easily aspirated using US guidance [338]. US-guided GC intra-bursal injection is effective and safe for treating refractory Achilles enthesitis in patients with SpA [339].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Additionally, color Doppler ultrasound facilitates the observation of internal structure changes and blood flow in lymph nodes. [4,5] The versatility of color Doppler ultrasound technology is evident in various clinical diagnostic applications. [6] Alis et al [7] investigated the efficacy of Superb microangiography and power Doppler ultrasound in diagnosing synovial inflammation of the knee joint in patients with juvenile idiopathic arthritis, with power Doppler ultrasound imaging demonstrating superiority.…”
Section: Introductionmentioning
confidence: 99%